Insight into the high-temperature tribological mechanism of VAlTiCrW high entropy alloy film: AlV3O9 from tribochemistry - Xuesong Liu; Jun Fan; Jibin Pu; Zhaoxia Lu (Friction)
Abstract High-entropy alloys have made significant progress in high mechanical properties, wear resistance, and corrosion resistance properties. Excellent tribological properties, especially high-temperature lubrication, have become another sought performance. In this work, VAlTiCrW high-entropy alloy film with body-centered cubic (BCC) structure was prepared on superalloy substrate by magnetron sputtering. It is found that the VAlTiCrW film shows very low friction coefficient of 0.15 and a low wear rate of 10−5 orders of magnitude at 800 °C. After 800 °C oxidation, the film can still obtain a friction coefficient of no more than 0.2 at 700 °C. XRD and TEM revealed the formation of ternary oxide AlV3O9 with preferred orientation of (002) crystal plane with large spacing of 0.71 nm on the wear surface of the film, a high-temperature lubricating phase that has not been reported, realizes the low friction coefficient. This AlV3O9 can be formed by tribochemical reaction under the thermal-mechanical action at 700 °C, but pre-oxidation at 800 °C is the prerequisite in order to form the precursors of V-rich and Al-rich oxide layer.